PENGUATAN PERAN PETUGAS KESEHATAN: IMPLEMENTASI KELEMBAGAAN DAERAH DALAM MENINGKATKAN KESEHATAN KELUARGA PRASEJAHTERA DI MATARAM - Chairun Nasirin (Jurnal PRIMA, 2017)
The implementation of local public health workforce focuses in improving the quality of low-income family regarding healthy and the future prosperity and better life and health of family. The low-income family phenomenon as an escalating worldwide problem for developing countries. This is due to an offspring of the modern urban of modern world era and country disaster. Understanding the problem of the low income family that emerge from social complex and health department of the local government and the broader community building to overcome the health government problems. Key Words: Health of local worker, health Development, Low income family